Optimalisasi Layanan ForYou Wedding Organizer: Menilai Kepuasan Konsumen - Lena Sopia; Anggalia Wibasuri (Penerbit Goodwood, 2025)
Purpose: The purpose of this study is to e xamine consumer satisfaction based on the expected value and performance of the ForYou Wedding Organizer service. Methodology/approach: This research is a quantitative research using a descriptive method. The data source used in the research process is primary data. The population in this study is all consumers of ForYou Wedding Organizer services. Sampling in this study uses the purposive sampling method 100 sample. The analysis tool uses the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. Results/findings: The results of the study show that several attributes that are included in quadrant I in the Cartesian diagram, namely: safety and comfort attributes are detected and attributes provide correct and accurate information. The results of the Customer Satisfaction Index (CSI) of the overall level of consumer satisfaction, and obtained a C SI value of 76.02%, it can be concluded that overall consumers are satisfied with the performance of the attributes of the ForYou Wedding Organizer service. Conclusion: The study finds that transaction security, convenience, and accurate information are key priorities for service improvement. With a CSI score of 76.02%, customers are generally satisfied, indicating opportunities for continuous service enhancement and stronger customer loyalty. Limitations: The focus of the research is only on the aspect of consumer satisfaction, so other aspects such as customer loyalty, marketing effectiveness, or the quality of relationships with vendors are not analyzed in depth. Contribution: This study succeeded in identifying the main factors that affect the satisfaction of ForYou Wedding Organizer consumers, such as Tangibles, Reliability, Responsiveness, Assurance, Emphaty.